2018
DOI: 10.17159/2519-0105/2018/v73no5a3
|View full text |Cite
|
Sign up to set email alerts
|

Applying the perceptions of graduates on their dental training to inform dental curricula from the perspective of occupational health

Abstract: introduction: Dental education, one of the most stressful fields of study, is associated with many occupational health hazards. Clinical training is focussed on patient care and occurs under the supervision of a qualified practitioner, and is thus the most appropriate time to educate students about the prevention of occupational health problems. The study aimed to report on the reflections of dental graduates on their undergraduate training from the perspective of occupational health. Methods: This cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…the fair distribution of the limited resources to many. 6 In effect, adhering to ethical principles can be stressful to an ethical, caring and dedicated clinician who has to provide medical and dental services in keeping with available finances rather than according to their "ideal" training and clinical reasoning. A recent survey amongst dentists working under conditions where there were limited resources for dental treatment confirmed that some of the major personal stressors arose from their ethical concerns of being faced with working in a "survival culture" where they were compelled to deliver in terms of patient numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the fair distribution of the limited resources to many. 6 In effect, adhering to ethical principles can be stressful to an ethical, caring and dedicated clinician who has to provide medical and dental services in keeping with available finances rather than according to their "ideal" training and clinical reasoning. A recent survey amongst dentists working under conditions where there were limited resources for dental treatment confirmed that some of the major personal stressors arose from their ethical concerns of being faced with working in a "survival culture" where they were compelled to deliver in terms of patient numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The four principles include: respect for patient autonomy; beneficence; non-maleficence and justice. 5,6 When considering beneficence and non-maleficence, it is important to remember that this does not only refer to the "good or damage" associated with the physical treatment, but includes psycho-social benefits, and financial and biological costs.…”
Section: Introductionmentioning
confidence: 99%
“…To contribute efficiently and successfully to the community as a health-care professional, the dentist should be efficient not only in their clinical practice but also in the nonclinical aspects of the practice. [ 5 ] The previous study conducted in the US, the Netherlands, Mexico, and France had a lack of nonclinical discrepancies including their financial status, time and their management, and their practice health and effective management among dental students. [ 6 7 ] The team formed by us has very high apprehension and experimentation experience that made it into the finest publications[ 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 ] The following study evaluates opinions from dental students on the requirement of practice management (PM) in the undergraduate (UG) dental program.…”
Section: Introductionmentioning
confidence: 99%